THE EFFECTS OF IRON DEFICIENCY ANEMIA ON BONE MINERAL DENSITY AND LABORATORY DATA IN PATIENTS WITH OSTEOPOROSIS - Ferda Özdemir; Özlem Tükenmez; Nesrin Turan (Archives of Rheumatology, 2003)
Life style, eating habits, chronic diseases and therapy methods of these diseases might possibly cause bone density changes and osteoporosis (OP). Iron deficiency and iron deficiency anemia might be accepted as risk factors. In our study, we aimed to investigate whether there was any association between bone mineral density (BMD), laboratory values and iron deficiency / iron deficiency anemia among postmenopausal women and senile osteoporosis. One hundred forty-one women, who were enrolled in our osteoporosis outpatient clinic, were found to be eligible for this study. The demographic data of the patients were recorded. Total blood count, serum iron (Fe), total iron binding capacity (TIBC), transferrin saturation (TS), serum folic acid (FA) and vitamin B12 levels were measured. Fourteen women out of 141 postmenopausal women with osteoporosis were found to have anemia (9.93 %). There were significant differences in Ca, Mg, Fe, TS levels between two groups. There was a difference in TIBC levels between two groups but it wasn’t significant. In this study, there was no significant difference in bone mineral densities between two groups. In the patient group with iron deficiency anemia, negative correlation was found between Fe and Ca levels. No association could not be found between anemia parameters and bone mineral densities in both groups. According to the results of this study, although there was a negative correlation between Fe and Ca levels in postmenopausal women with iron deficiency anemia and osteoporosis, it didn’t make an obvious impact to the bone mineral density.